ANALISIS PREFERENSI SISWA MELANJUTKAN STUDI KE MTs PONDOK PESANTREN DARUSSALAM KECAMATAN KABUN KABUPATEN ROKAN HULU TAHUN AJARAN 2014/2015 - Darmayana Senja, Sry Darmayana Senja Sry; Yakub, Elni Yakub Elni; Saam, Zulfan Saam Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research has done to know what the preference of students are, to continue their lesson to Mts( boarding school) PondokPesantren Darussalam Kabun. According to the internal factors and external factors, the benefits of this research are:1)The information that we get from this research will use for the counseling guidance teachers in their jobs, 2)For parents, as consideration for directing children choose the next school.3)To disseminate information as early as possible about MtsPondokPesantren Darussalam Kabun.The sample in this research is the students of Mts Pondok Pesantren Darussalam Kabun, wich were 75 students by using descriptive methode. The research result showeed that generally the students choose to study in Mts is to deepen on Koran and want to continue their study in Arabia. Key Words: Preference, boarding school, MTs